2019
DOI: 10.1093/ecco-jcc/jjz200
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effect of Urine-derived Stem Cells on Inflammatory Bowel Diseases via Downregulating Th1/Th17 Immune Responses in a PGE2-dependent Manner

Abstract: Background and Aims Despite the therapeutic promise of stem cell therapy in the treatment of inflammatory bowel diseases [IBD], most donor cell populations have to be obtained via invasive approaches and often remain insufficiently validated. Urine-derived stem cells [USC] were recently shown to have regenerative properties and can be harvested in a safe, low-cost, and noninvasive way. This study aims to evaluate the immunomodulatory effect of USC and their efficacy in the management of IBD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 58 publications
2
38
0
Order By: Relevance
“…Numerous immune responses have been implicated in the beneficial effect associated with cell therapy with MSCs. 6–10 In this study, we examined whether these beneficial effects are also maintained in the long term in a clinically relevant experimental model of colitis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous immune responses have been implicated in the beneficial effect associated with cell therapy with MSCs. 6–10 In this study, we examined whether these beneficial effects are also maintained in the long term in a clinically relevant experimental model of colitis.…”
Section: Resultsmentioning
confidence: 99%
“…Regardless of the h-aMSC dose used and day of infusion of the h-aMSCs, a similar degree of colitis attenuation was observed in all instances, which accords with previous results published in the literature. 6 , 14 , 28 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stem cells, like USCs, could be beneficial based on their immunoregulatory effect controlling inflammation[ 86 ]. Indeed, Zhou et al[ 87 ] demonstrated that implantation of USCs in a rodent model reduced inflammatory bowel diseases. Systemic administration of USCs significantly ameliorated the clinical and histopathological severity of colitis and increased the survival rate in both acute and chronic murine colitis models.…”
Section: Uscs: Applicationsmentioning
confidence: 99%
“…MSCs can also inhibit monocyte differentiation into dendritic cells and skew them to a tolerogenic profile [ 19 ]. Moreover, effects of MSCs on suppression of T helper 1 (Th1) cells and Th17 proliferation [ 20 ] together with regulatory T cells (Tregs) expansion have also been documented in many inflammatory conditions [ 21 ].…”
Section: Introductionmentioning
confidence: 99%